Variability and Processes of the Denmark Strait Overflow - Macrander, Andreas (2004)
The Atlantic Meridional Overturning Circulation (AMOC) is considered as an important part of the global climate system. The densest component of the AMOC is the Denmark Strait Overflow Water, entering the deep Atlantic across the sill between Greenland and Iceland. Here, four years of overflow measurements in Denmark Strait are analyzed. The data suggest, that the overflow consists of a density driven, hydraulically controlled part, and a barotropic, wind stress forced component. The observed overflow transport reduction of 20% from 1999 (3.7 Sv) to 2003 (3.1 Sv) is likely caused by both a dense water reservoir height decrease in the Iceland Sea, and a reduction of the local wind stress forcing. The interannual fluctuations are consistent with a reduction of the North Atlantic Oscillation (NAO). Interannual temperature variability of 0.5 °C is linked to variable upstream entrainment rates and/or variable percentages of different water masses rather than changes of the individual sources. Further, an anticorrelation with the Faroe Bank Channel Overflow is found, with the total dense water outflow from the Nordic Seas being almost constant at 5.5 Sv from 1999 to 2003.